Burundi : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper (PRSP II). (IMF Staff Country Reports; Country Report ;, 2012)
The Joint Staff Advisory Note gives positive feedback on the elaborations made in Burundi's Poverty Reduction Strategy Report (PRSR-II), and commends the measures taken to eliminate the implementation weaknesses and pitfalls of PRSR-I. The note puts forth guidelines to be followed by the government in implementation of the strategies for achieving the desired results, and emphasizes the need for ensuring a broad social consensus. The Executive Board also emphasizes the need for prioritizing the areas for further development.